The efficiency of different storage methods for a producer of antistaphylococcal antibiotic batumin promising for industrial-scale production - Churkina, L.N.; Avdeeva, L.V.; Yaroshenko, L.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Variability of properties and antibiotic activity, and the cells survival of Pseudomonas batumici, a producer of batumin (an antistaphylococcal antibiotic), after the long-term storage under a vaseline oil layer and in a lyophilized state were studied. The main morphological, physiological, and biochemical properties of the mutant strain were explored. It was found that both methods of storage provided high level of antibiotic activity of the strain-producer – 160–170 mg/ml, at that the method of storage in the lyophilized state provided higher level of cells survival in population. The method of batumin-producing strain lyophilization will allow to create a bank of cultures with high biosynthetic activity, which may provide a long-term guaranteed cell suspension production.